2018
DOI: 10.1039/c8ra05480k
|View full text |Cite|
|
Sign up to set email alerts
|

Zr–Cu alloy filler metal for brazing SiC ceramic

Abstract: The Zr–Cu filler metal is mainly used for the joining of SiC ceramic as a nuclear fuel cladding material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The results of XRD analysis are shown in Figure 3. It can be found that new phases ZrC and Zr2Si are formed at different temperatures, which are in accordance with the results of thermodynamic calculation and analysis [18]. At the same time, the amount of reaction products increases with the increase of the brazing temperature.…”
Section: Brazing Temperaturesupporting
confidence: 86%
See 4 more Smart Citations
“…The results of XRD analysis are shown in Figure 3. It can be found that new phases ZrC and Zr2Si are formed at different temperatures, which are in accordance with the results of thermodynamic calculation and analysis [18]. At the same time, the amount of reaction products increases with the increase of the brazing temperature.…”
Section: Brazing Temperaturesupporting
confidence: 86%
“…The equilibrium wetting angle of Zr-Cu filler metal on the SiC ceramic surface by wetting experiment is maintained at about 5° with the prolongation of holding time. It is shown that the filler metal can well wet SiC ceramic, and the interface reaction layer is growing [18]. The elements Zr and Si diffuse Figure 6b, the fracture of the brazed joint is brittle fracture, and the fracture position mainly occurs in the interface reaction layer, with a certain number of SiC particles on the fracture surface.…”
Section: Holding Timementioning
confidence: 98%
See 3 more Smart Citations